Illegitimate bodies? Turner syndrome and the silent interplay of age, gender, and generational positions - Diasio, Nicoletta (Frontiers in Sociology, 2023)
This paper focuses on the strength of social norms that define the right development of the body in time. It also analyzes how the social positions of age, gender and generation intertwine in the definition of such a legitimate body. The starting point is anthropological research carried out in France between 2018 and 2020 among girls and women affected by Turner syndrome, a rare genetic condition causing small stature, ovarian insufficiency, a delay or absence of puberty, and infertility. We first explore how measuring the body has become central in the social construction of the concept of age-appropriateness. We then present four women' narratives, which express various forms of desynchronization: the gap between physical appearance, chronological age and age status; the cleft between the physical development induced by hormone therapy and being in a particular stage in life; the difference between chronological and reproductive age; and lastly, the trouble in a generational position related to infertility. For women suffering from this genetic condition, the gap between bodies, time and social statuses associated with age, gender and generation, may engender a feeling of “being out of place.” The alignment of body and time is then one of the bastions of essentialization and naturalization. Finally, we stress the complex interplay of bodily and social markers of age and gender, and their role in social relations as both a resource and a constraint. Thus, while the syndrome may cause distress and sometimes a lack of legitimacy, it also leads to a critical re-examination of hegemonic models of womanhood and their intersection with age positions.